Nile red and DCM fluorescence Anisotropy studies in C12E7/DPPC mixed systems - Coutinho, Paulo J. G. (2002)
The lipid/surfactant mixed interactions between the lipid dipalmitoylphosphatydilcholine (DPPC) and the non-ionic surfactant C12E7 [C12H25(OCH2CH2)7OH] were studied by the use of fluorescence anisotropy of Nile Red and DCM laser dye. Three different regions, consisting of mixed micelles, mixed vesicles and both aggregates, were identified. Nile Red fluorescence anisotropy is wavelength dependent, the spectra being decomposed in two log-normal functions. These results are consistent with a solvent relaxation process, with distinct anisotropies for the relaxed and unrelaxed states. The spectral properties (anisotropy and maximum emission wavelength) of the relaxed state show higher sensitivity to the environment than those of the unrelaxed state. DCM fluorescence anisotropy show similar trends. This was interpreted as a result of a trans-cis photoisomerization process. The observed anisotropy spectrum was decomposed in two gaussian functions, reflecting a distinct anisotropy for each isomer.